2006
DOI: 10.1177/0361198106195200108
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Stabilization of High-Sulfate Soils in Texas

Abstract: In an effort to construct roads more quickly, high-plasticity index soils stabilized with lime are now routinely compacted the day after mixing. With this practice has come an increasing number of heaves due to soluble sulfates reacting with the lime to form ettringite. Soils with sulfate concentrations below 7,000 to 8,000 parts per million (ppm) can generally be treated with lime. This research was performed to identify stabilizers that can be used with sulfate concentrations above 10,000 ppm. The effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…These challenges include: stabilisation of sulfate soils containing larger amounts of sulfates (more than 8000 ppm); methods to screen sulfates in real field conditions; and development of devices that could provide faster screening and assessments of sulfate heave in treated soils. Recent studies reported by Harris et al (2006) introduced a new field testing methodology to screen and determine soluble sulfates and the method has shown early promise. Other challenges are currently under research evaluation and the research results are expected to be reported in the literature over the coming years.…”
Section: New Developments and Challengesmentioning
confidence: 99%
“…These challenges include: stabilisation of sulfate soils containing larger amounts of sulfates (more than 8000 ppm); methods to screen sulfates in real field conditions; and development of devices that could provide faster screening and assessments of sulfate heave in treated soils. Recent studies reported by Harris et al (2006) introduced a new field testing methodology to screen and determine soluble sulfates and the method has shown early promise. Other challenges are currently under research evaluation and the research results are expected to be reported in the literature over the coming years.…”
Section: New Developments and Challengesmentioning
confidence: 99%
“…As for ES, addition of the product modified the behaviour of the soil during the compaction. Nevertheless, field and laboratory testing confirmed the ability of lignosulfonate to be leached out of the soil [11,22,27]. So, it is to be expected that the soil will recover its initial characteristics after a certain period of time.…”
Section: Discussionmentioning
confidence: 99%
“…However, Harris et al [11] showed that the 3-D swelling potential of a plastic clay (PI = 51) was not modified by the addition of 0.07% of an ES treatment. Another stabilisation mechanism was suggested by Velasquez et al [32], who observed that an ES could have surfactant properties and thus stabilise the soil by improving its compaction ability.…”
Section: B Enzymatic Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson and Miller (1992) classified the soil having linear shrinkage strain over 15 percent as high risky soil to the infrastructure damage. In accordance with the procedure (Harris, 2008), the 3-dimensional swell test was conducted to gauge swelling potential that would cause the soil volume change due to moisture migration. The result indicates that the subgrade soils of sections "S1" and "S2" are more susceptible to swelling than section "S3" soil.…”
Section: Materials Characterizationmentioning
confidence: 99%